EVALUATION OF MORPHOLOGICAL AND GROWTH CHARACTERISTICS AMONG THREE KOREAN NATIVE BLACK GOAT STRAINS - Eun-Do Lee; Byamungu Mayange Tomple; Dong-Kyo Kim; Ga Eun Kim; Bong Hwan Choi; Kwan-Woo Kim (Journal of Animal and Plant Sciences, 2025)
The study aimed to investigate and compare the morphological and growth characteristics of three Korean native black goat strains: Dangjin, Jangsu, and Tongyeong. The objective was to test the hypothesis that each strain exhibits unique physical and growth traits, reflecting their genetic and environmental adaptations. These insights are intended to support conservation strategies by providing baseline data essential for the preservation and selective breeding of these genetic resources. A total of 804 goats were assessed from 2010 to 2022, with data collected on coat color, presence of wattles, horn structure, body weight, and measurements (body length, depth, chest width, and chest girth) at various growth stages (birth, 3, 6, 9, and 12 months of age). Body weights and measurements were recorded using a calibrated digital scale and tape measure, respectively, with each goat measured individually by trained personnel to minimize error. Morphological characteristics were noted based on visual inspection. For statistical analysis, a one-way analysis of variance (ANOVA) was conducted using the General Linear Model (GLM) procedure to assess the fixed effects of strain, sex, and age on various growth characteristic variables; and results were presented as means ± standard deviation (SD). The data revealed that they possessed horns and displayed black or dark brown coat colors, but rarely exhibited wattles. Birth weights were generally consistent across strains, though the Tongyeong strain had the lowest birth weights. At 12 months, males and females in the Tongyeong strain significantly exhibited lower body weights and smaller body measurements compared to the Dangjin and Jangsu strains, highlighting a notable distinction in growth patterns among the strains (p<0.05). Across all strains, male goats were generally larger than females, with body length and depth measurements showing similar trends (p<0.05). Overall, the findings suggest that the Tongyeong strain is characterized by a smaller body size at comparable growth stages, potentially reflecting unique genetic or environmental adaptations within this strain.
Keywords: Genetic resources; Growth characteristics; Korean native black goat; Morphology